1903
DOI: 10.1098/rsta.1903.0006
|View full text |Cite
|
Sign up to set email alerts
|

VI. The fracture of metals under repeated alternations of stress

Abstract: It is well known that metals will break down under repeated application, and especially under repeated reversal, of stresses greatly less than those that have to he applied when the “ultimate strength” of the material is tested in the ordinary way. The researches of Wöhler have shown, for example, that iron capable of bearing about 20 tons per sq. inch of steady load will break when it is exposed to some millions of reversals of a stress of 8 or 9 tons per sq. inch, alternately in compression and extension. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…A fundamental step regarding fatigue as a material problem was made in the beginning of the 20 th century by Ewing and Humfrey in 1903 [1]. They carried out a microscopic investigation which showed that fatigue crack nuclei start as microcracks in slip bands.…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental step regarding fatigue as a material problem was made in the beginning of the 20 th century by Ewing and Humfrey in 1903 [1]. They carried out a microscopic investigation which showed that fatigue crack nuclei start as microcracks in slip bands.…”
Section: Introductionmentioning
confidence: 99%
“…The multistage strength degradation theory, which has recently emerged from studies on the material and structural behaviour of concrete [1,2], provides a clear description of the fatigue mechanism that has been the focus of extensive research since the early nineteenth century [3][4][5]. According to this theory, fatigue is caused by the sporadic sudden change of cracking behaviour in a system under cyclic loading, leading to intermittent strength reduction of the system and its eventual failure.…”
Section: Introductionmentioning
confidence: 99%
“…Further work by Ewing and Humfrey (1903) reported that slip bands appeared in materials at stress levels below the yield stress after a few stress reversals. After further * cycling, more bands appeared and the original bands broadened.…”
Section: Traditional Approachmentioning
confidence: 99%